Cloning and sequencing of gene encoding hyaluronidase from the venom of Apis mellifera - SHEN Li-rong; ZHANG Chuan-xi; CHENG Jia-an (浙江大学学报. 农业与生命科学版, 2002)
The venomous hyaluronidase (AmHya) gene of Italian honey bee (Apis mellifera) collected in China was amplified by RT-PCR from total RNA of venom glands of the worker bee. Sequence analysis showed the gene was composed of 1 149 nucleotides. The alignment of the amino acid sequence of AmHya gene and 6 Hya genes from other organisms showed that AmHya is most closely related to the AcHya of Chinese honeybee (A. cerana cerana) with 91% amino acid level identity. A phylogenetic tree of 7 Hyaluronidases was drawn by using GENETYX program, and molecular structures and functions of these ensymes were compared and analysed.